2020
DOI: 10.3389/fphar.2020.549150
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Protease Activated Receptor 1 Is Involved in the Hemostatic Effect of 20(S)-Protopanaxadiol by Regulating Calcium Signaling

Abstract: in PPD-induced platelet aggregation by regulating calcium signaling. Collectively, our study could provide the new insights of PPD as an essential hemostatic ingredient in Panax notoginseng for the treatment of hemorrhagic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Platelet function reagents for thrombin (Chrono-Log Corporation, Pennsylvania, USA) and Fluo-3 AM calcium indicators (Beyotime Biotechnology, Shanghai, China) were used in this study. measured in two mice models [4,28]. 40 male Kunming mice were randomly divided into five groups, including normal saline (NS), hemocoagulase (HC), and PD groups with different doses of 2, 4, and 8 mg/kg PD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Platelet function reagents for thrombin (Chrono-Log Corporation, Pennsylvania, USA) and Fluo-3 AM calcium indicators (Beyotime Biotechnology, Shanghai, China) were used in this study. measured in two mice models [4,28]. 40 male Kunming mice were randomly divided into five groups, including normal saline (NS), hemocoagulase (HC), and PD groups with different doses of 2, 4, and 8 mg/kg PD.…”
Section: Methodsmentioning
confidence: 99%
“…Blood Routine Test. Blood samples from 40 Wister male rats (200:0 ± 10:0 g) of five groups, including NS, HC, and PD groups (2, 4, and 8 mg/kg) were withdrawn from the abdominal aorta and placed in an anticoagulant tube with EDTA to perform routine blood analysis by using the XT-2000i automated hematology analyzer (Sysmex Corporation, Japan), as described previously [4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…But, until now, few studies have shown that 20(S)-PD affects the blood system. We have found in previous study that PPD can promote the hemostatic of model bleeding rats and induce platelet aggregation by regulating calcium signaling [19]. Gao et al reported that PPD increased ADP-induced platelet aggregation [10].…”
Section: Introductionmentioning
confidence: 91%